Dietary Crude Protein and Total Digestible Nutrient on The Performance of Boerka Goats Male Growing Phase - Rijanto Hutasoit; Solehudin Solehudin; SP Ginting; K Simanihuruk; S Zubaidah; Sumarni Sumarni (The Faculty of Veterinary Medicine of Syiah Kuala University, 2021)
Boerka goat is the best meat type goat. Feed quality is one of the biggest factors that affect productivity, so it is necessary to know in advance the need for nutrients. The purpose of this study was to determine the dietray of crude protein (CP) and Total Digestible Nutrients (TDN) in efficient feed for the production of Boerka goats male growing phase. This study was designed in a completely randomized design, consisting of six combination feed treatments with six replications. Namely: 1 (CP 13.00% and TDN 63.10%); 2 (CP 13.03% and TDN 65.07%); 3 (CP 13.00% and TDN 70.00%); 4 (CP 15.00% and TDN 62.69%); 5 (CP 15.12% and TDN 65.00%); 6 (CP 15.00% and TDN 70.00%). The observed variables were feed consumption, feed consumption ratio (FCR), nutrient digestibility (dry matter, organic matter, crude protein) and average daily gain (ADG). Results of this study show that the balanced of CP and TDN has no significant effect on consumption and FCR. However, it was significantly different for digestibility and ADG. Feed treatment (CP 13.03% and TDN 65.07%) obtained the higher digestibility of DM and OM (71.49 and 70.5%), while the highest CP digestibility was treated with CP 15.05% and TDN 62.69% (71.59%). The ADG response of Boerka goats with CP 13.03% and TDN 65.07% was the good results (144.90 g head-1day-1) while the lowest response was on CP 13.08% and TDN 63.10%. It is concluded that the dietray of CP 13.03% and TDN 65.07% is a recommended of Boerka goat male growing phase.